Myocardial revascularization Controversy over noninvasive and invasive detection of ischemia - Gaede, Luise; Blumenstein, Johannes; Moellmann, Helge (Herz, 2022)
With some exceptions, myocardial revascularization in patients with chronic coronary syndrome (CCS) is generally decided on the basis of the extent of myocardial ischemia. Current data indicate that a patient will benefit from revascularization if ischemia is present in more than 10% of the myocardium. Accordingly, all patients presenting with CCS should undergo a noninvasive ischemia test that can answer this question before diagnostic coronary angiography. In order to be able to make a recommendation for revascularization based on scientific data even in those patients who previously had no clear evidence of ischemia, e.g., because of discrepant findings, measurement of the hemodynamic significance of coronary stenoses with a lumen diameter reduction >= 50% should be performed during coronary angiography. A decision to revascularize based on hemodynamic significance was shown to be beneficial to patients in several studies.
CRIS-Team WoS Importer:2022-05-13